The development of social entrepreneurship and the perspective of its further affirmation in the overall development of Serbia - Mitrović, Jovan; Mitrović, Vladimir (Anali Ekonomskog fakulteta u Subotici, 2020)
The model of social economy in Europe is expanding and gaining momentum, and can thus be considered as one of the pillars of European integration project. The holders of this economy are various actors who, individually or jointly, create associations, organizations, cooperatives or enterprises that will satisfy the needs of target social groups or communities. The paper explains the essence of social entrepreneurship and follows its development and role in the economy life of Serbia. Several examples of social enterprises are given, who provide social services in innovative ways, solve the problems of marginalized groups, environment protection, as well as the ways of organizing new business models within the model of franchise integration. In a separate part, incentive developmental factors as well as limitations following the development of social entrepreneurship are identified. Finally, on the basis of the analysis of social entrepreneurship, with the aim of its further affirmation in Serbia, the measures that economic, social and political decision makers should implement are given.